Ethics in medical education digital scholarship: AMEE Guide No. 134. (3rd March 2020) - Masters, Ken
Abstract: Ethics has long been a concern in medicine, education and scholarship. In the digital age, new complexities have arisen, and many medical education researchers are unprepared for the pitfalls ahead, often negotiating these in the absence of guidelines, and unaware of the many tools that can be used to assist them. This Guide takes the medical education scholar through a journey in which issues of ethics are discussed in all stages of digital scholarship: research preparation, research subject monitoring and data gathering, securing one's data (and balancing security against accessibility), anonymising textual and non-textual data, third party identifiability in digital data, writing one's own work (including plagiarism and paper mills), copyright (including issues of Creative Commons and royalty-free), accessing inaccessible reference material, ethically citing electronic material, and manuscript submission (including issues of selecting journals, open access and data sharing). The Guide ends with a brief look to the future. This Guide aims to be a useful tool to alert the readers to some of the most important ethical issues that need to be considered, and some practical solutions to ethical problems faced, when engaging in medical education digital scholarship.